Long-Term Deformation Monitoring of Metro-Tunnel Airshaft Excavation during Construction Stage - L. Ran; T. H. Yi; X. W. Ye; X. B. Dong (International Journal of Distributed Sensor Networks)
The project of Hangzhou Metro Line 1 is the first metro line of the urban rapid rail transit system in Hangzhou, China, which is one of the largest municipal projects of Hangzhou and is being constructed commencing from March 28, 2007 and expected to be completed by October 1, 2012. This metro line has a total length of 48 km and 34 stations, connecting Hangzhou downtown with the suburban area of the city. Owing to the complex geological condition, harsh construction situation, and immature computational methodology, construction of metro systems is often subjected to considerable sources of uncertainties. To ensure the safety of the adjacent building structures, it is a vital necessity to monitor deep excavations of metro tunnels at their in-construction stage. This paper introduces the instrumentation system for settlement monitoring of a metro-tunnel airshaft of the project of Hangzhou Metro Line 1 during the construction of deep excavation. The long-term settlement data monitored by the measurement markers installed at the surface ground and in the depth direction of the airshaft excavation construction site are analyzed and presented in detail. The obtained results indicate that the settlements at the instrumented locations of the construction site during different construction steps vary steadily in an allowable variation range.